STRUKTUR DAN KOMPOSISI VEGETASI SEKITAR SARANG PENYU HIJAU (Chelonia mydas Linnaeus) PANTAI PANGUMBAHAN, SUKABUMI SELATAN, JAWA BARAT - Roemantyo Roemantyo; Adriani Sri Nastiti; Ngurah N Wiadnyana (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Pangumbahan coastal area is one of many important nesting sites of the green turtle (Chelonia mydas Linnaeus) in Indonesia. This area is mainly comprises of disturb coastal old secondary forest. Some sites along the seashore were converted into fishpond, dry land agricultural and other was destroyed for other uses or as an open unproductive areas. However this area has a still plays an important role especially for the conservation of green turtle habitat and also for the ecosystem stabilization of the coastal area in general. Floristic research was conducted on September 2009 to investigate the existing vegetation structure and composition along the seashore using transects method.The â€œpoint center quarters methodâ€ was used to calculate the importance value of the vegetation on every turtle nesting sites. The important natural species vegetation communities in the area were comprises of herbs, shrubs and trees species. Ipoemoea pes-caprae (L.) R. Br and Spinifex littoreus (N. L. Burman) Merrill as a first layer coastal line plant community that play as an important herbs species which creeping grown on the white sands coastal surface. The second layer comprises herbs, small trees and shrubs such as Pandanus tectorius Parkinson ex Zucc, Crinum asiaticum L. and Callotropis gigantea R.Br. The second layer species plays as a vegetation community which covering and protecting the green turtle nest site from the direct sunshine, running of big wave and heavy rain water. Terminalia catappa L., Calophyllum inophyllum L., Barringtonia asiatica (L.) Kurz. and Hibiscus tiliaceus L. as a big crown tree community grown covering on the most behind as a back layer of coastal line which play as shading trees of the second layer species community, especially to stabilized humidity and temperature of the sand and the environment. The vegetation structure and composition of the old secondary coastal forest of Pangumbahan was described to understand the detail role and function of the vegetation species in this area.